Understanding the Service Quality and Brand Creditability: A Case Study of Laundry Service with Challenging the Behavioral Loyalty in Bangkok Area - Jitsoonthornchaikul, Muenjit (Connexion: Journal of Humanities and Social Sciences, 2023)
The most achieved business today are said to have strong customer loyalty. However, how challenged to create behavioral loyalty into brand. This research paper studies about behavioral loyalty is committed to repeat purchasing, make recurring income and provide sustainable business. To explore three underlying concepts: service quality, brand creditability, and consumer loyalty in the context of laundry service in Bangkok area. The mediating effect of service quality, brand credibility and consumer loyalty were also tested. A total of 240 valid questionnaires was collected via purposive sampling method and analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM). This research employed the Analysis of Moment Structures (AMOS) version 21.0. Results indicate that service quality has a positive influence on brand credibility, whiles brand credibility and service quality do not strengthen behavioral loyalty. The results for practical implications also indicate that service quality has a positive influence on brand credibility, whiles brand credibility and service quality do not directly strengthen behavioral loyalty. However, service quality have strengthened through brand creditability have influenced to behavioral loyalty. Its originality or value, this research utilizing the value of service quality and brand credibility which combine the brand image, brand identity, including behavioral loyalty. The examination of consumer behavior provides valuable insights for marketing strategies in terms of word of mouth spreading, frequency of App, website visiting, and influencer or reviewer sharing in digital society.